New species of Acroneuria (Plecoptera: Perlidae) from central Vietnam - Chen, Zhi-Teng (Zootaxa, 2020)
Three new species of Acroneuria Pictet, 1841, A. axana sp. nov., A. songhaitiani sp. nov., and A. taygianga sp. nov. are described and illustrated from Quang Nam Province of central Vietnam. The three new species are diagnosed based on wing pattern, aedeagal structure, and shape of the female subgenital plate. Morphological differences between the three new species and known congeners are indicated. A distribution map of known species of Acroneuria from Vietnam is provided.